POLITENESS STRATEGIES IN STUDENT`S LANGUAGE OF AS`ADIYAH ERENG ISLAMIC BOARDING SCHOOL, BANTAENG DISTRICT - Anwar; Ikhwan M. Said; Gusnawaty (International Journal of Social Science, 2022)
Language has the important role in the process of communication in the community. Language politeness is the most appropriate thing to use in communication, because with polite language a person is able to maintain the value and dignity of himself and others. The use of polite language needs to be improved, especially among students who are in the public spotlight that students when interacting prioritize language politeness. In interaction and communication, politeness is one of the important aspects to be raised. Politeness aims to create good relationships and communication in social interaction between speakers and addressees. Both are intended to generate respect for oneself and others, so that the level of politeness will affect the values ​​and perspectives of others towards him. In addition, people will further strengthen the relationship between two. Islamic boarding school is a multilingual society. The diversity of language used by the students is clearly visible when communicating orally. This diversity occurs due to differences in the background of each student. Therefore, researchers are interested in conducting research in Islamic boarding schools. This research is entitled "Politeness Strategies in Students Language Of As`adiyah Ereng Islamic Boarding School, Bantaeng Regency". This study aims to describe forms of language politeness strategy for elevent graders in interaction in surroundings of As`adiyah ereng Islamic boarding school Bantaeng Regency in forman situation and nonformal situation using the perspective or theory of Brown Levinson (1987). This type of research is a type of qualitative research with a descriptive design. The technique used in collecting data in this study was carried out with observation techniques, recording techniques, and note-taking techniques. Data analysis through interpretation. The results of this study indicate that there are (7) bald on-record strategies, (12) positive politeness strategies, (4) negative politeness strategies, (1) off-record strategies, in this study there are also (3) silent strategies, the conclusion of this research is bald on-record as a politeness strategy most often used by students in both formal and non-formal situations. As a suggestion based on this research, it is expected that students pay attention to politeness in language so that they reflect polite language. For further researchers, this thesis can be used as an additional reference for further research.